Foreseeing postoperative pain in neurosurgical patients: pupillometry predicts postoperative pain ratings: an observational study - Vide, Sérgio (2020)
Pupillary reflex dilation (PRD) is triggered by noxious stimuli and diminished by opioid administration. In the postoperative period, PRD has been shown to be correlated with pain reporting and a useful tool to guide opioid administration. In this study we assessed whether pupillary measurements taken before extubation were related with the patient's reported pain in the Post-Anesthesia Care Unit (PACU) using the Numerical Rating Scale (NRS). Our objective was to evaluate the correlation of PRD and pupillary variables measured intraoperatively with postoperative pain under the same opioid concentration. This was a prospective observational study of 26 neurosurgical patients undergoing general anesthesia exclusively with propofol and remifentanil. A portable infrared pupillometer was used to provide an objective measure of pupil size and PRD (using the Pupillary Pain Index) before extubation. Pain ratings were obtained from patients after recovery of consciousness, while remifentanil was maintained at 2 ng/mL. A significant correlation was observed between NRS scores and pre-extubation PPI (rS = 0.62; P = 0.002), as well as between NRS scores and pupil diameter before tetanic stimulation PPI (rS = 0.56, P = 0.006). We also found a negative correlation between pupil diameter and age (rS = - 0.42, P = 0.04). The statistically significant correlation between pre-extubation PPI scores and NRS scores, as well as between the pupillary diameter before tetanic stimulation and NRS scores suggest the possibility of titrating analgesia at the end of the intraoperative period based on individual responses. This could allow clinicians to identify the ideal remifentanil concentration for the postoperative period.